Movements from Pearl Rivers : Connections flowing between Southern China and Aotearoa : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Creative Arts at Massey University, Palmerston North, New Zealand - Ma'auga, Tessa (Massey University, 2023)
According to ancient worldviews indigenous to China, the universe and humanity evolved and diversified from one single origin, inheriting a divinely spiritual, as well as physical reality. The familial ties binding all life within the universe operate according to principles of reciprocity, harmony in diversity, and balance. These indivisible relationships continue across realms between deceased ancestors and living descendants. The role of humanity to cultivate the divine attributes reflected in the universe is aided by the advancement of arts and crafts. Such perspectives have informed this creative research, which unravels genealogical, philosophical, cultural, and artistic connections that flow between Southern China and Aotearoa. The visual outcome of the research, Movements from Pearl Rivers exhibition, highlights principles which propelled the long historical evolution of Southern China and her descendants. The continuously unfolding narrative of Southern China from cosmological origins, through ancient Austronesian migrations, to the 19th century Southern Chinese global dispersal is conveyed through a site-specific installation which threads together fibres connecting this region such as mulberry paper, banana, bamboo, silk, and flax. Paper cutting scrolls, kinetic cascading cords, woven items, and the objects and stories contributed by eight diverse descendants of the 19th century Southern Chinese global dispersal reinforce a spirit of connection flowing between an ancestral homeland in Southern China and a present homeland in Aotearoa. This research contributes to prevalent art discourses within Oceania which are learning to embrace the increasingly complex, diverse, and cross-cultural identities and relationships of this region. The conceptual framework based on elements of a Chinese cosmological worldview is offered in communication with diverse wisdom traditions in Oceania. The framework centres artistic practice on the cultivation of beautiful attributes within both the artist and their materials, for the purpose of fostering harmonious relationships. The artworks emphasise the notion of the ever-flowing spirit, underlying and connecting all beings within the universe.
Images are reproduced with permission.
Listed in 2023 Dean's List of Exceptional Theses
Keywords: Site-specific installations (Art); New Zealand; Palmerston North; Influence (Literary, artistic, etc.); Philosophy, Chinese; Aesthetics, Chinese; Influence; Art; Oceania; Ma'auga, Tessa; Movements from Pearl Rivers; Dean's List of Exceptional Theses; 360602 Fine arts